Patinkin as a reader of Keynes' General Theory: Are wage cuts a good remedy to unemployment?1. Issue 6 (1st November 2016) - Rivot, Sylvie
Abstract: This paper analyses Patinkin's appraisal of Keynes' concept of involuntary unemployment while focusing on his reading of the General Theory Chapter 19. On several critical issues, Patinkin departs from Keynes' original matters of concerns. He leans against an individual criterion for unemployment and implicitly endorses Wicksell's understanding of voluntary unemployment as chosen leisure. His appraisal of involuntary unemployment as a disequilibrium phenomenon ultimately relies on nominal rigidities and assumes the existence of a competitive adjustment process. On all these three critical points, Patinkin departs from Keynes but also initiates the contemporary New Keynesian programme that went even further from Keynes.